Risks in the budget management fund education service Bogotá (2014)
This article has the purpose of knowing which the risks of the background Education service in Bogota are. Furthermore, about the budget management and impact generated in the institution. This investigation is based on the comparison of budget execution concerning two public schools of 2013. In this research is known and analyzes the risks that arise in the management of public resources in the ESF, which was performed by direct observation and document review, analyzing the procedures performed at educational institutions in budget management Demonstrating that the greatest risks arising in the ESF are creating a negative impact on the institution, being the taking of decisions by the Rector and the committee of Directors one of the most important risks since they are targeted according to the guidelines dictated by the principal, which is due to that you do not possess enough for budget execution knowledge. In addition to this, there are not with the respective committees that allow you to exercise control over the management of resources